Polynomial Asymptotics of Entire Functions of Finite Order - Borova, O. I.; Zabolotskii, N. V.; Боровая, О. И.; Заболоцкий, М. В.; Боровая, О. И.; Заболоцкий, М. В. (Institute of Mathematics, NAS of Ukraine, 2003)
We obtain new asymptotic relations for entire functions of finite order with zeros on a ray under the condition of regular growth for the counting function of their zeros. These relations improve the well-known results of Valiron.